2013
DOI: 10.1158/1078-0432.ccr-12-1779
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Sorafenib in Patients with Platinum-Pretreated, Advanced (Stage IIIb or IV) Non–Small Cell Lung Cancer with a KRAS Mutation

Abstract: Purpose: Sorafenib inhibits the Ras/Raf pathway, which is overactive in cancer patients with a KRAS mutation. We hypothesized that patients with non-small cell lung cancer (NSCLC) with KRAS mutation will benefit from treatment with sorafenib.Experimental Design: In this phase II study, patients with KRAS-mutated, stage IIIb or IV NSCLC that progressed after at least one platinum-containing regimen were treated with sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 42 publications
(44 reference statements)
1
57
0
Order By: Relevance
“…Sorafenib is an oral multitarget TKI which inhibits RAF and related transmembrane receptors. Phase II trials showed promising results with a disease control rate of ∼50% [25,26,28]. Yet subgroup analyses performed in the KRAS-mutated group of the phase III MISSION trial did not reveal any specific efficacy of sorafenib in the third or fourth chemotherapy line [27].…”
Section: If Direct Blocking Of Rasmentioning
confidence: 99%
“…Sorafenib is an oral multitarget TKI which inhibits RAF and related transmembrane receptors. Phase II trials showed promising results with a disease control rate of ∼50% [25,26,28]. Yet subgroup analyses performed in the KRAS-mutated group of the phase III MISSION trial did not reveal any specific efficacy of sorafenib in the third or fourth chemotherapy line [27].…”
Section: If Direct Blocking Of Rasmentioning
confidence: 99%
“…Clinical trials of sorafenib in patients with advanced non-smallcell lung cancer have demonstrated modest activity, with no survival advantage (7,20). Though it is attractive to consider ARAF/ RAF1 mutations as possible biomarkers of sorafenib response in lung adenocarcinoma, additional profiling and functional characterization studies will be required to establish this link.…”
Section: Figurementioning
confidence: 99%
“…Analysis of TA performance by Kuiper et al [32] in serum from 50 chemotherapy-naïve patients treated with erlotinib plus sorafenib [33] again confirmed superior outcomes for patients classified as good outcome versus poor outcome (OS: 13.7 vs. 5.6 months; HR: 0.30; p 5 .009; PFS: 5.5 vs. 2.7 months; HR: 0.40; p 5 .035), whereas the objective RR was not significantly different [32]. For sorafenib monotherapy, as reported by Dingemans et al in 55 pretreated patients, PFS was significantly longer in TA-discerned good-outcome patients versus poor-outcome patients (2.6 vs. 1.5 months; HR: 1.4; p 5 .029), whereas OS was not significantly different (6.0 vs. 2.5 months; HR: 1.3; p 5 .166), probably due to a relatively large variation in OS duration [34]. Stinchcombe et al applied the TA to sera of 98 elderly patients treated in a randomized phase II trial of first-line therapy with gemcitabine, erlotinib, or combination [64].…”
Section: Studies Reporting Profiling Prior To Systemic Therapymentioning
confidence: 87%